The Ph.D. Dilemma in Canada Revisited - Von Zur-Muehlen, Max (Canadian Journal of Higher Education, 1978)
Growth of doctoral studies at Canadian universities in the last two decades has resulted in the more than 1,000 programs that are now offered. Not surprisingly, the output of Ph.D. graduates has increased 6 fold since the early sixties. But during the seventies, an imbalance between the rising supply of Ph.D. 's and the declining demand for them, particularly in higher education, became apparent. This paper traces historical trends in the employment of Canada's Ph.D. holders, and looks at their prospects for the future. Traditionally, about 65% of doctoral graduates have entered educational occupations. Today, because of the youthful age structure, there are few retirements or deaths, and hence, the annual replacement demand is for only about 500 Ph.D. 's. But Canadian universities now confer around 2,000 doctorates each year (including returning Canadians from abroad). Moreover, this imbalance is apt to persist. On the basis of the current enrolment of 13,000, the Ph.D. supply has been projected from 1977-78 to 1981-82 for 45 disciplines. Relating these supply estimates to the likely demand for university teachers reveals a potential surplus in almost every discipline. A cycle of shortage and surplus appears to have developed in some fields. These simulations have been derived from assumptions, which are outlined in two appendices and 26 supporting tables. In addition, this paper also examines other features of the Ph.D. situation in Canada: a history of the growth of graduate education; variations in the ratio of Ph.D. enrolment to graduates in different disciplines; support programs for doctoral students, and the immigration of university teachers. The information provides an overview of the many dimensions of the Ph.D. issue.